Electret, electret filter, and method for producing electret film
Patent Information
- Application Number
- JP2024079202
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-05-15
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-03-04
AI Technical Summary
【0012】 本発明のエレクトレット及びエレクトレットフィルタは帯電性能に優れる。また、本発明の方法によれば、帯電性能に優れるエレクトレットフィルムを製造することができる。
Smart Images

Figure 0007632730000001 
Figure 0007632730000002 
Figure 0007632730000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an electret, an electret filter, and a method for producing an electret film. [Background technology]
[0002] Conventionally, films having electrostatic properties have been suitably used as various air purifying filters for the purpose of collecting dust particles in the air by electrostatic force. As a required characteristic of these electrostatically charged films, excellent particle collection efficiency due to high electrostatic properties is strongly desired. As a method for imparting electrostatic properties to such films, electret treatment by corona discharge and electrostatic imparting method by friction are known, and electrostatic properties can be imparted to the film by carrying out these electrical processing treatments. Attempts have been made in the past to enhance the electrostatic properties by adding various additives to the resin film before carrying out the above-mentioned electrical processing treatments.
[0003] For example, Patent Document 1 discloses a triboelectrically charged filter medium made of polyester fibers and polyolefin fibers containing a phosphorus-based additive and a sulfur-based additive.
[0004] Patent Document 2 also describes a compound having a thermoplastic resin and a formula Y 2 -A(R 1 ) n - an electret filter medium comprising a compound of formula Y1 (I), where A is benzene, naphthalene, or anthracene, and Y 1 and Y 2 are each independently R 2 -R 3 and R 2 is an ester or amide linking group, R 3 is an alkyl group having 10 to 22 carbon atoms, R 1 is R 2 -R 3 where R 2 and R 3are each independently as defined above, and when A is benzene, n is 0 to 4, when A is naphthalene, n is 0 to 6, and when A is anthracene, n is 0 to 8).
[0005] Furthermore, Patent Documents 3 and 4 disclose electret webs containing electrostatic charge additives containing heterocyclic imides.
[0006] Also, Patent Document 5 discloses an electret web containing a charge enhancing additive that contains a divalent metal-containing substituted mercaptobenzimidazolate salt.
[0007] According to Patent Documents 1 to 5, by adding various additives to a resin for the purpose of enhancing charging performance, it is possible to enhance charging performance compared to a case where no additives are added. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2013-049021 A [Patent Document 2] Special Publication No. 2009-526141 [Patent Document 3] Special Publication No. 2012-522908 [Patent Document 4] Special Publication No. 2012-522909 [Patent Document 5] Special Publication No. 2016-509137 Summary of the Invention [Problem to be solved by the invention]
[0009] In the above Patent Documents 1 to 5, various additives are used in the resin for the purpose of enhancing the charging performance, but there is still room for improvement in terms of dispersibility and charging performance.
[0010] The problem to be solved by the present invention is to provide an electret and an electret filter having excellent charging performance, and also to provide a method for producing an electret film having excellent charging performance. [Means for solving the problem]
[0011] The present invention relates to the following: [1] An electret comprising a propylene-based resin and an amide compound represented by the following formula (1): R 1 -NHCO-R 2 -CONH-R 3 (1) (In formula (1), R 2 is an aromatic dicarboxylic acid residue represented by the following formula (2), and R 1 and R 3 each independently represents an alicyclic hydrocarbon group which may have a substituent. [ka] [2] The electret according to [1] above, wherein the amide compound is 2,6-naphthalenedicarboxylic acid dicyclohexylamide. [3] The electret according to [1] or [2] above, having β-crystal activity. [4] The electret according to any one of the above [1] to [3], having a saturated charging voltage of 7.5 kV or more. [5] An electret filter comprising fibers comprising a propylene-based resin and an amide compound represented by the following formula (1): R 1 -NHCO-R 2 -CONH-R 3 (1) (In formula (1), R 2 is an aromatic dicarboxylic acid residue represented by the following formula (2), and R 1 and R 3 each independently represents an alicyclic hydrocarbon group which may have a substituent. [ka] [6] The electret filter according to the above [5], wherein the amide compound is 2,6-naphthalenedicarboxylic acid dicyclohexylamide. [7] The electret filter according to [5] or [6] above, wherein the fibers have β-crystal activity. [8] The electret filter according to any one of the above [5] to [7], having a saturated charging voltage of 7.5 kV or more. [9] An air purifier comprising the electret filter according to any one of the above items [5] to [8].
[10] (a) preparing a film containing a propylene-based resin and an amide compound represented by the following formula (1); (b) imparting an electric charge to the film The method for producing an electret film comprising the steps of: R 1 -NHCO-R 2 -CONH-R 3 (1) (In formula (1), R 2 is an aromatic dicarboxylic acid residue represented by the following formula (2), and R 1 and R 3 each independently represents an alicyclic hydrocarbon group which may have a substituent. [ka]
[11] The method for producing an electret film according to the above
[10] , wherein the amide compound is 2,6-naphthalenedicarboxylic acid dicyclohexylamide.
[12] The method for producing an electret film according to the above
[10] or
[11] , wherein the step of providing an electric charge is a discharge treatment. Effect of the Invention
[0012] The electret and electret filter of the present invention have excellent charging properties. Moreover, according to the method of the present invention, an electret film having excellent charging properties can be produced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, embodiments for carrying out the present invention (hereinafter simply referred to as "the present embodiment") will be described in detail. The following present embodiment is an exemplification for explaining the present invention and is not intended to limit the present invention to the following content. The present invention can be appropriately modified and implemented within the scope of its gist. In addition, in this specification, the term "A to B" regarding the description of numerical values means "A or more and B or less" (when A < B) or "A or less and B or more" (when A > B). In the present invention, a combination of preferable embodiments is a more preferable embodiment.
[0014] <Electret> An electret (hereinafter also referred to as "Product 1") according to an example of a preferred embodiment of the present invention contains a propylene-based resin and an amide compound represented by the following formula (1). Product 1 is formed of a resin material (hereinafter also referred to as "the present material") containing a propylene-based resin and an amide compound represented by the following formula (1). R 1 —NHCO—R 2 —CONH—R 3 (1) (In formula (1), R 2 is an aromatic dicarboxylic acid residue represented by the following formula (2), and R 1 and R 3 are each independently an alicyclic hydrocarbon group which may have a substituent.)
Chemical formula
[0015] <Electret filter> Further, an electret filter (hereinafter also referred to as "Product 2". Also, "Product 1" and "Product 2" are collectively referred to as "Product") according to an example of another preferred embodiment of the present invention contains fibers containing a propylene-based resin and the amide compound represented by the above formula (1). Product 2 is formed of a material containing fibers containing the present material.
[0016] (Propylene-based resin) Examples of the propylene-based resin include homopolypropylene (propylene homopolymer), and random or block copolymers of propylene and α-olefins such as ethylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, or 1-decene. Among these, homopolypropylene is more preferably used from the viewpoint of mechanical strength.
[0017] The isotactic pentad fraction of the propylene resin is preferably 80 to 99 mol%, more preferably 83 to 98 mol%, and even more preferably 85 to 97 mol%. The isotactic pentad fraction indicates stereoregularity, and if the isotactic pentad fraction is 80 mol% or more, the mechanical strength is good. On the other hand, the upper limit of the isotactic pentad fraction is specified by the upper limit value that can be obtained industrially at present, but this will not be the case in the future when a resin with higher regularity is developed at an industrial level. The isotactic pentad fraction refers to the three-dimensional structure or the proportion thereof in which the five methyl groups, which are side chains, are all located in the same direction relative to the main chain formed by carbon-carbon bonds composed of any five consecutive propylene units. The assignment of signals in the methyl group region is in accordance with A. Zambelli et al., Macromol., 8, 687 (1975).
[0018] The Mw / Mn of the propylene-based resin is preferably 1.5 to 10.0, more preferably 2.0 to 8.0, and even more preferably 2.0 to 6.0. Mw / Mn is a parameter indicating molecular weight distribution, and the smaller the Mw / Mn, the narrower the molecular weight distribution. By making the Mw / Mn 1.5 or more, sufficient extrusion moldability is obtained, making industrial mass production possible. On the other hand, by making the Mw / Mn 10.0 or less, sufficient mechanical strength can be ensured. Mw / Mn is measured by the GPC (gel permeation chromatography) method.
[0019] The melt flow rate (MFR) of the propylene-based resin is not particularly limited, but is preferably 0.5 to 15 g / 10 min, more preferably 1.0 to 10 g / 10 min, and even more preferably 1.5 to 5.0 g / 10 min. By setting the MFR to 0.5 g / 10 min or more, sufficient melt viscosity is obtained during molding and high productivity can be ensured. On the other hand, by setting the MFR to 15 g / 10 min or less, sufficient strength can be ensured. The MFR is measured in accordance with JIS K7210-1 (2014) at a temperature of 230°C and a load of 2.16 kg.
[0020] The method for producing the propylene-based resin is not particularly limited, and examples thereof include a known polymerization method using a known polymerization catalyst, for example, a polymerization method using a multi-site catalyst such as a Ziegler-Natta catalyst or a single-site catalyst such as a metallocene catalyst.
[0021] Examples of propylene-based resins that can be used include commercially available products such as those sold under the trade names "Novatec PP," "WINTEC," and "WAYMAX" (manufactured by Japan Polypropylene Corporation); "Versify," "Notio," and "Tafmer XR" (manufactured by Mitsui Chemicals, Inc.); "Zelas" and "Thermorun" (manufactured by Mitsubishi Chemical Corporation); "Sumitomo Noblen" and "Tafthren" (manufactured by Sumitomo Chemical Co., Ltd.); "Prime Polypro" and "Prime TPO" (manufactured by Prime Polymer Co., Ltd.); "Adflex," "Adsyl," and "HMS-PP (PF814)" (manufactured by SunAllomer Co., Ltd.); and "Inspire" (manufactured by The Dow Chemical Company).
[0022] The content of the propylene-based resin in the product is preferably 50% by mass or more, more preferably 70 to 99.9999% by mass, even more preferably 80 to 99.999% by mass, and still more preferably 90 to 99.99% by mass.
[0023] (Other resins) The material may contain resins other than the propylene-based resin as long as the effects of the present invention are not impaired. Examples of other resins include polystyrene resins, polyvinyl chloride resins, polyvinylidene chloride resins, chlorinated polyethylene resins, polyester resins, polycarbonate resins, polyamide resins, polyacetal resins, acrylic resins, ethylene vinyl acetate copolymers, polymethylpentene resins, polyvinyl alcohol resins, cyclic olefin resins, polylactic acid resins, polybutylene succinate resins, polyacrylonitrile resins, polyethylene oxide resins, cellulose resins, polyimide resins, polyurethane resins, polyphenylene sulfide resins, polyphenylene ether resins, polyvinyl acetal resins, polybutadiene resins, polybutene resins, polyamideimide resins, polyamide bismaleimide resins, polyarylate resins, polyetherimide resins, polyether ether ketone resins, polyether ketone resins, polyether sulfone resins, polyketone resins, polysulfone resins, aramid resins, and fluorine-based resins.
[0024] The content of other resins in the product is preferably 10% by mass or less, more preferably 5% by mass or less, and preferably 1% by mass or less.
[0025] (Amide compound represented by formula (1)) In the formula (1), R 1 and R 3 The alicyclic hydrocarbon group represented by the formula (I) may be polycyclic or monocyclic, and examples thereof include a cycloalkyl group, a cycloalkenyl group, and a cycloalkynyl group. More specific examples thereof include a cycloalkyl group having 3 to 8 carbon atoms, a bicycloalkyl group having 6 to 12 carbon atoms, a bicycloalkenyl group having 6 to 12 carbon atoms, a spiroalkyl group having 6 to 12 carbon atoms, and a tricyclic tricycloalkyl group having 10 to 14 carbon atoms.
[0026] R 1 and R 3The alicyclic hydrocarbon group represented by the formula (I) may have a substituent. Examples of the substituent include a halogen atom such as a fluorine atom or a chlorine atom; a cyano group; a substituted amino group such as a dimethylamino group; an alkoxy group having 1 to 6 carbon atoms such as a methoxy group, an ethoxy group, an isopropoxy group; a nitro group; an alkyl group having 1 to 8 carbon atoms such as a methyl group, an ethyl group, an isopropyl group, a t-butyl group; an aryl group such as a phenyl group or a naphthyl group; a -C(=O)-OR group; and a -SOR group. R represents an alkyl group having 1 to 6 carbon atoms such as a methyl group, an ethyl group, a propyl group, or an aryl group having 6 to 14 carbon atoms such as a phenyl group or a naphthyl group.
[0027] From the viewpoints of dispersibility with propylene resin, excellent electrostatic performance, and structural stability, R 1 and R 3 The alicyclic hydrocarbon group represented by the formula (I) is preferably a cycloalkyl group which may have a substituent. Examples of the cycloalkyl group which may have a substituent include cycloalkyl groups having 3 to 8 carbon atoms, such as a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, and a cyclooctyl group. Among them, from the viewpoint of structural stability, a cyclohexyl group which may have a substituent is more preferable.
[0028] Examples of the substituent of the cycloalkyl group which may have a substituent include an alkyl group having 1 to 8 carbon atoms, such as a methyl group, an ethyl group, an isopropyl group, a t-butyl group, etc.; an alkoxy group having 1 to 6 carbon atoms, such as a methoxy group, an ethoxy group, a isopropoxy group, etc.; a halogen atom, such as a fluorine atom, a bromine atom, a chlorine atom, etc.; an aryl group, such as a phenyl group, a naphthyl group, etc.; a C(=O)-OR group; and a -SOR group, etc. R represents an alkyl group having 1 to 6 carbon atoms, such as a methyl group, an ethyl group, a propyl group, etc.; or an aryl group having 6 to 14 carbon atoms, such as a phenyl group, a naphthyl group, etc.
[0029] More specifically, examples of such cycloalkyl groups include alkoxycycloalkyl groups such as 2-methoxycyclopropyl and 3-ethoxycyclohexyl; alkylthiocycloalkyl groups such as 2-methylthiocyclopropyl and 3-ethylthiocyclohexyl; and halogenated cycloalkyl groups such as 2-chlorocyclopropyl and 3-bromocyclohexyl.
[0030] Among the above-mentioned amide compounds, 2,6-naphthalenedicarboxylic acid dicyclohexylamide is the most preferable from the viewpoints of dispersibility in the propylene-based resin and excellent charging performance.
[0031] The reason why the electret and electret filter of the present invention can exhibit excellent charging performance by containing the amide compound represented by the formula (1) is not necessarily clear, but the present inventors speculate as follows.
[0032] Generally, highly polar compounds such as amide compounds have a problem in that they are poorly dispersible in propylene-based resins having low polarity due to electrostatic interactions, and tend to aggregate. However, the amide compound represented by the formula (1) has the property of dissolving in a propylene-based resin in a certain temperature range. Due to this property, the amide compound is uniformly dispersed in the propylene-based resin, and crystals derived from the compound are easily precipitated uniformly. Therefore, it is considered that the crystals of the amide compound having high polarity are uniformly dispersed in the propylene-based resin having low polarity, and high charging properties can be obtained.
[0033] In addition, the amide compound represented by the formula (1) has a rigid R 2 It is believed that the ferroelectricity is caused by the molecular rotation of the amide chains around the axis, resulting in polarization reversal. 1 and R 3If R is an alicyclic hydrocarbon group such as a cycloalkyl group, it is believed that phase transition occurs more easily and that it exhibits excellent ferroelectricity compared to a straight-chain alkyl group. The amide compound represented by the above formula (1), which is believed to have such ferroelectricity, generates high polarization through discharge treatment inside the propylene-based resin, and the bias in the charge generated there is believed to greatly contribute to improving the chargeability of the entire propylene-based resin. Furthermore, 1 and R 3 When is a cycloalkyl group, bond angle distortion and torsional distortion are eliminated within the structure, and therefore structural stability can be expected.
[0034] (β crystal activity) The present product 1 preferably has β-crystal activity. Also, the fiber comprising the present material contained in the present product 2 preferably has β-crystal activity. The β-crystal activity of this product can be regarded as an index showing that the propylene-based resin in the nonporous membrane has generated β-crystals. If the propylene-based resin in the nonporous membrane has generated β-crystals, the crystals of the highly polar amide compound are uniformly dispersed in the propylene-based resin with low polarity, and this product can have high charging properties.
[0035] The presence or absence of β-crystal activity in this product is judged by whether or not the crystal melting peak temperature derived from the β-crystal of the propylene-based resin is detected using a differential scanning calorimeter. Specifically, when the product is heated in a differential scanning calorimeter from 25°C to 240°C at a heating rate of 10°C / min and held for 1 minute, then cooled from 240°C to 25°C at a heating rate of 10°C / min and held for 1 minute, and then heated again to 25°C to 240°C at a heating rate of 10°C / min., if a crystal melting peak temperature (Tmβ) derived from the β crystals of the propylene-based resin is detected during re-heating, it is determined to have β crystal activity.
[0036] The presence or absence of the β crystal activity can also be determined from a diffraction profile obtained by X-ray diffraction measurement of the present product that has been subjected to a specific heat treatment. In detail, the product is subjected to heat treatment at 170 to 190°C, which is a temperature exceeding the crystal melting peak temperature of the propylene-based resin, and then slowly cooled to generate and grow β crystals. When the product is subjected to X-ray diffraction measurement and a diffraction peak derived from the (300) plane of the β crystals of the propylene-based resin is detected in the range of 2θ = 16.0° to 16.5°, it is judged to have β crystal activity. For details on the β crystal structure of the propylene-based resin and X-ray diffraction measurement, Macromol.Chem., 187, 643-652 (1986), Prog.Polym.Sci., Vol.16, 361-404 (1991), Macromol.Symp., 89, 499-511 (1995), Macromol.Chem., 75, 134 (1964), and references cited in these documents can be referred to.
[0037] The β-crystal activity of the present product based on the β-crystal generating ability is preferably 40% or more, more preferably 60% or more, even more preferably 75% or more, and even more preferably 80% or more. The upper limit of the β-crystal activity is not particularly limited, but the closer to 100%, the more preferable. The higher the β-crystal activity, the more β-crystals of the propylene-based resin are generated. As a result, crystals of the highly polar amide compound are uniformly dispersed in the propylene-based resin having a low polarity, and the present product can have high charging properties. The β-crystal activity is determined as the ratio of ΔHmβ to the total of the detected heat of crystal fusion ΔHmα derived from α-crystals and the heat of crystal fusion ΔHmβ derived from β-crystals. Specifically, the β-crystal activity is measured by the method described in the examples below.
[0038] The amide compound represented by the formula (1) can act as a β-crystal nucleating agent, and can promote the formation and growth of β-crystals of the propylene-based resin.
[0039] The content of the amide compound represented by the formula (1) in the product is preferably 0.0001 to 5.0 parts by mass, more preferably 0.001 to 3.0 parts by mass, and even more preferably 0.01 to 1.0 parts by mass, based on 100 parts by mass of the propylene-based resin in the product. If it is 0.0001 parts by mass or more, β crystals of the propylene-based resin can be sufficiently generated and grown during production, and sufficient β crystal activity can be ensured. On the other hand, if it is added in an amount of 5.0 parts by mass or less, it is economically advantageous and there is no bleeding of the β crystal nucleating agent onto the electret surface, which is preferable.
[0040] In addition, as long as the effect of the present invention is not impaired, other β-crystal nucleating agents than the amide compound represented by the formula (1) may be further blended. The other β-crystal nucleating agents are not particularly limited, and known ones can be used. The content of the other β-crystal nucleating agent in the product can be appropriately adjusted depending on the type of β-crystal nucleating agent or the composition of the propylene-based resin, etc., but the total of the amide compound represented by the formula (1) and the other β-crystal nucleating agent is preferably 0.0001 to 5.0 parts by mass, more preferably 0.001 to 3.0 parts by mass, and even more preferably 0.01 to 1.0 part by mass, per 100 parts by mass of the propylene-based resin in the product.
[0041] (Additives, etc.) The material may contain various additives within a range that does not impair the effects of the present invention. Examples of additives that are added for the purpose of improving or adjusting moldability, productivity, and various physical properties of the porous film include recycled resins generated from trimming losses such as selvages, inorganic particles such as silica, talc, kaolin, and calcium carbonate, pigments such as titanium oxide and carbon black, flame retardants, weather resistance stabilizers, heat resistance stabilizers, antistatic agents, melt viscosity improvers, crosslinking agents, lubricants, nucleating agents, plasticizers, antioxidants, antioxidants, light stabilizers, ultraviolet absorbers, neutralizing agents, antifogging agents, antiblocking agents, slip agents, and colorants.
[0042] (Electrets and electret filters) According to the present invention, since a material having high dispersibility and excellent charging performance, including a propylene-based resin and a specific amide compound, is used, an electret and an electret filter having excellent charging performance can be obtained. In addition, since the polyamide compound has β-crystal activity, an electret and an electret filter having excellent strength can be obtained.
[0043] This product is obtained by charging the material and semi-permanently retaining the charge (electretization). The electretization method may be a charging method such as corona discharge, electric field discharge, electron beam irradiation, or frictional charging, or a combination of these. Among these, corona discharge is preferred because it allows simple and high-strength charging.
[0044] The shape and form of the product are not particularly limited, and it may be in any form, such as a film, sheet, fiber (filament), strand, woven fabric, or nonwoven fabric.
[0045] The electretization can be carried out in a state where the material has been molded and processed into the shape of the final product, but it is also possible to convert the material into an electret in the state of an intermediate molded product and then process it into the shape of the final product. When the material is charged in the form of a film, the film may be defibrated into a fibrous form after charging, and the charged fibrous form may then be made into strands or processed into textile fabrics.
[0046] (1) Thickness When the product is a film, sheet, or other film, its thickness is not particularly limited, but is preferably 10 μm or more, more preferably 50 μm or more, and is preferably 1000 μm or less, more preferably 750 μm or less, and even more preferably 500 μm or less. If the thickness is 10 μm or more, the film can retain sufficient strength, and if the thickness is 1000 μm or less, the film has excellent handleability.
[0047] (2) Porosity When the product is a film, the porosity is preferably 10% or less, more preferably 5% or less, and even more preferably 1% or less. The porosity is a value indicating the ratio of the space in the film. If the porosity is 10% or less, it is possible to prevent water vapor from entering the inside of the film, and it is preferable because the electrostatic property can be maintained for a long period of time. The porosity was measured by the following method. The actual mass W1 of the measurement sample is measured, and the mass W0 when the porosity is 0% is calculated based on the density of the resin composition. The porosity is calculated from these values based on the following formula. Porosity (%)={(W0-W1) / W0}×100
[0048] (3) Air permeability When the product is a film, its air permeability is not particularly limited, but is preferably 30,000 sec / dL or more, more preferably 60,000 sec / dL or more, and even more preferably 90,000 sec / dL or more. If the air permeability of the film is 30,000 sec / dL or more, it is possible to prevent water vapor from entering the inside of the film, and thus it is preferable that the electrostatic charge can be maintained for a long period of time.
[0049] "Air permeability" indicates the difficulty of air passing through the film in the thickness direction, and is specifically expressed as the number of seconds required for 100 mL of air to pass through the film. Therefore, a smaller value means that it is easier to pass through, and a larger value means that it is harder to pass through. In other words, a smaller value means that the film has good interconnectivity in the thickness direction, and a larger value means that the film has poor interconnectivity in the thickness direction. Interconnectivity is the degree of connection of the pores in the thickness direction of the film. The air permeability (sec / 100 mL) can be measured in accordance with JIS P8117:2009, specifically, by the method described in the Examples.
[0050] (4) Saturation charging voltage The saturated charging voltage of the present product is preferably 7.5 kV or more, more preferably 7.7 kV or more, and even more preferably 8.0 kV or more. If the saturated charging voltage of the present product is 7.5 kV or more, high dust collection properties can be expected when used, for example, as an air purifier filter.
[0051] The layer structure of the product is not limited to a single layer, and may further include other layers in a multi-layer structure of two, three, four, five or more layers, as long as the effects of the present invention are not significantly impaired.
[0052] <Production method for this product 1> Below, the manufacturing method of the present product 1 will be explained using an electret film as an example, but the following explanation is only one example of a method for manufacturing the present product, and the present product 1 is not limited to an electret film manufactured by such a manufacturing method.
[0053] <Method of manufacturing electret film> The method for producing an electret film of the present invention (hereinafter also referred to as "Production Method 1") includes (a) a step of producing a film containing a propylene-based resin and an amide compound represented by the following formula (1), and (b) a step of imparting an electric charge to the film. R 1 -NHCO-R 2 -CONH-R 3 (1) (In formula (1), R 2 is an aromatic dicarboxylic acid residue represented by the following formula (2), and R 1 and R 3 each independently represents an alicyclic hydrocarbon group which may have a substituent. [ka]
[0054] The present production method 1 is sufficient as long as it includes at least the above steps (a) and (b), and may further include other steps or treatments.
[0055] (Step (a)) The step (a) is a step of producing a film. The raw material used in the production of the film may be, for example, the present material. When kneading the present material, there is no particular limitation on the machine used. For example, a known extruder such as a single screw extruder, a twin screw extruder, or a multi-screw extruder may be used. Depending on the equipment structure and necessity, a pressure reducer may be connected to the vent port to remove moisture and low molecular weight substances.
[0056] Examples of methods for heating and melting the present material include the T-die method and the inflation method, among which the T-die method is preferred. For practical purposes, it is preferred to melt-extrude the present material from a T-die and cast it using a cast roll.
[0057] As a specific method for forming a film, when the T-die method is used, sheet-shaped molten resin extruded from a T-die is laminated and then pulled up while being in close contact with a rotating cast roll (chill roll, cast drum) to be formed into a sheet-like material.
[0058] In order to adhere the film-like material to the casting roll, a touch roll, an air knife, an electric adhesion device, or the like may be attached to the casting roll. When the kneaded material is cooled and molded into a film, the temperature of the casting roll is preferably 100° C. or higher, more preferably 110° C. or higher, and even more preferably 120° C. or higher. In this production method 1, in order to obtain sufficient β-crystal activity, it is preferable to set the temperature of the casting roll to 100° C. or higher and obtain a film-like material with a high degree of crystallinity.
[0059] The obtained film may be uniaxially or biaxially stretched. The uniaxial stretching may be longitudinal uniaxial stretching or transverse uniaxial stretching. The biaxial stretching may be simultaneous biaxial stretching or sequential biaxial stretching. From the viewpoint of controlling the porous structure, it is preferable to adopt sequential biaxial stretching. Note that stretching in the machine direction (MD) of the sheet is called "machine stretching", and stretching in the direction perpendicular to the machine direction (TD) is called "transverse stretching". The stretching temperature and stretching ratio can be appropriately selected.
[0060] (Step (b)) The step (b) is a step of providing an electric charge to the film obtained in the step (a). The obtained film is subjected to an electric charging treatment to obtain the present product 1. The electric charging treatment in this case may be a continuous type or a batch type, and may be any charging method such as corona discharge, electric field discharge, electron beam irradiation, or frictional charging, or may be a combination of these charging methods, but a discharge treatment is preferred.
[0061] The electrodes used in the charging process may be a method in which the film is passed between electrodes such as needle electrodes, wire electrodes, roll electrodes, and plate electrodes on the front and back of the film and an electric field is applied between the electrodes, or a method in which electrodes are formed directly on the front and back of the film by coating or vapor deposition and then an electric field is applied. The electric field to be applied is preferably 0.1 MV / m to 10 MV / m, more preferably 0.2 MV / m to 8 MV / m, and even more preferably 0.3 MV / m to 6 MV / m. When the electric field is 0.1 MV / m or more, excellent charging properties can be obtained. When the electric field is 10 MV / m or less, there is an effect of reducing the dielectric breakdown during charging processing.
[0062] The product 1 may be further subjected to surface treatment such as corona treatment, plasma treatment, printing, coating, deposition, etc. as required, and may also be made into a laminate with perforations, etc. Also, several sheets of the product 1 may be stacked depending on the application.
[0063] <Production method for this product 2> The manufacturing method of Product 2, i.e., the manufacturing method of the electret filter of the present invention (hereinafter also referred to as "Production Method 2"), can be a method in which the electret film manufactured by Production Method 1 above is split to obtain split fibers, which are then carded into a nonwoven fabric sheet, and then needle punched, hot embossed calendared, ultrasonic welding, or the like to form an electret filter. The electret film may be split using a needle blade, a flat blade, a file blade, etc. The electret filter of the present invention may be used as a single material, but if necessary, it may be used by bonding it to a net, a nonwoven fabric, a woven fabric, etc. by needle punching, ultrasonic welding, or hot embossing calendaring.
[0064] <Use of this product> The product 1 can be used as an electrostatic element in electroacoustic devices such as microphones, headphones and speakers. The product 2 can also be used as an air purifying filter, for example in breathing apparatus, heating apparatus, ventilation apparatus (vehicles and buildings, etc.), air conditioning, and face masks. EXAMPLES
[0065] The electret of the present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited thereto.
[0066] (Propylene-based resin) A-1 Homopolypropylene ("Novatec PP FY6HA", MFR: 2.4g / 10min [230℃, 2.16kg load], Mw / Mn=3.2, Japan Polypropylene Corporation)
[0067] (Amide compounds) B-1 2,6-Naphthalenedicarboxylic acid dicyclohexylamide ("N-Jester NU-100", manufactured by New Japan Chemical Co., Ltd.)
[0068] (Antioxidants) C-1 A 1:1 mixture of tris(2,4-di-t-butylphenyl)phosphite and tetrakis[3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionic acid]pentaerythritol ("IRGANOX-B225", manufactured by BASF)
[0069] Example 1 Mixture 1 was obtained by mixing 100 parts by mass of a propylene-based resin (A-1), 0.2 parts by mass of an amide compound (B-1), and 0.1 parts by mass of an antioxidant (C-1) and melt-extruding the mixture at 280° C. using a twin-screw extruder. The mixture 1 was extruded at 200° C. using a T-die with a lip opening of 1 mm, and the mixture was guided to a cast roll to obtain a film-like product. Thereafter, the obtained film was placed on an earth plate, and a discharge treatment was carried out using needle electrodes with an inter-electrode distance of 20 mm to apply a voltage of 10 kV for 60 seconds to give the film a charge, thereby obtaining an electret film.
[0070] Comparative Example 1 A film-like material was obtained in the same manner as in Example 1, except that the amide compound (B-1) and the antioxidant (C-1) were not added, and then a discharge treatment was carried out to obtain an electret film.
[0071] The films obtained in the examples and comparative examples were measured for thickness, porosity, air permeability, β crystal activity, and saturated charging voltage by the following methods. The results are shown in Table 1.
[0072] (1) Film thickness A sample piece having a diameter of 40 mm was cut out from the measurement sample, and the thickness was measured at any five points on the film surface using a dial gauge with a graduation of 1 / 1000 mm, and the thickness was calculated from the average value.
[0073] (2) Porosity The actual mass W1 of the measurement sample was measured, and the mass W0 when the porosity was 0% was calculated based on the density of the resin composition. The porosity was calculated from these values based on the following formula. Porosity (%)={(W0-W1) / W0}×100
[0074] (3) Air permeability The air permeability was measured in accordance with JIS P8117:2009 in an air atmosphere at 25° C. The measuring device used was a digital Oken-type dedicated air permeability measuring device (manufactured by Asahi Seiko Co., Ltd.).
[0075] (4) β crystal activity The measurement sample was subjected to DSC measurement. First, the temperature is raised from 40 ° C. to 200 ° C. at 10 ° C. / min under a nitrogen atmosphere, held for 1 minute, and then cooled to 40 ° C. at 10 ° C. / min. After holding for 1 minute, the melting peak observed when the temperature is raised again at 10 ° C. / min is determined as the melting peak of β crystals when the peak exists in the temperature range of 145 to 157 ° C., and the melting peak observed at 158 ° C. or higher is determined as the melting peak of α crystals. The heat of fusion of each is calculated from the area of the region surrounded by the baseline and the peaks drawn based on the flat part on the high temperature side, and the heat of fusion of the crystals derived from α crystals is ΔHmα, and the heat of fusion of the crystals derived from β crystals is ΔHmβ, and calculated according to the following formula. β crystal activity [%] = [ΔHmβ / (ΔHmα+ΔHmβ)]×100
[0076] (5) Saturation charging voltage A sample piece measuring 10 cm in length and 1.5 cm in width was cut out from the measurement sample, fixed to a 0.8 mm thick polyethylene terephthalate substrate, and placed on an aluminum plate connected to earth. The sample piece was wiped with a wet cloth to remove static electricity, and then rubbed 10 times over a 5 cm section with a grounded nylon brush ("Static Electricity Removal Brush Hard A-1", manufactured by Trusco Nakayama Co., Ltd.) at a load of 250 g and a speed of 2 cm / sec to saturate the charge. The saturated charged measurement sample piece was left stationary for 20 minutes away from the aluminum plate to stabilize the charging voltage, and the saturated charging voltage was measured four times with a static electricity electrometer connected to earth, and the average value was taken as the saturated charging voltage. Even when the saturated charging voltage was measured at a negative voltage, the absolute value was taken as the measured value.
[0077] [Table 1]
[0078] From Example 1, since the electret containing the specific amide compound has a high saturated charging voltage, when it is used as, for example, an air purifier filter, it can be expected to have high dust collection properties. On the other hand, in Comparative Example 1, since the specific amide compound was not used, a sufficient saturation charging voltage could not be obtained. [Industrial Applicability]
[0079] The electret of the present invention is capable of collecting dust particles in the air by electrostatic force, and can be suitably used as various air cleaning filters.
Claims
1. An electret comprising a propylene-based resin and an amide compound represented by the following formula (1), having a saturated charging voltage of 7.5 kV or more and a porosity of 5% or less: R 1 ―NHCO―R 2 ―CONH―R 3 (1) (In formula (1), R 2 is an aromatic dicarboxylic acid residue represented by the following formula (2), and R 1 and R 3 each independently represents an alicyclic hydrocarbon group which may have a substituent. 【Chemistry 1】
2. 2. The electret according to claim 1, wherein the amide compound is 2,6-naphthalenedicarboxylic acid dicyclohexylamide.
3. The electret according to claim 1 or 2, having β crystal activity.
4. (a) preparing a film containing a propylene-based resin and an amide compound represented by the following formula (1), the film having a porosity of 5% or less; (b) A step of applying an electric field of 0.1 MV / m or more and 10 MV / m or less to the film to charge it, thereby obtaining an electret film having a saturated charging voltage of 7.5 kV or more. The method for producing an electret film comprising the steps of: R 1 ―NHCO―R 2 ―CONH―R 3 (1) (In formula (1), R 2 is an aromatic dicarboxylic acid residue represented by the following formula (2), and R 1 and R 3 each independently represents an alicyclic hydrocarbon group which may have a substituent. 【Chemistry 2】
5. The method for producing an electret film according to claim 4, wherein the amide compound is 2,6-naphthalenedicarboxylic acid dicyclohexylamide.
6. The method for producing an electret film according to claim 4 or 5, wherein the step of providing an electric charge is a discharge treatment.
Citation Information
Patent Citations
Air filter having novel filtering characteristics
JP1986204052A
Filter element for cleaning oil
JP1998015314A
Charged microfibers, microfibrillated articles and methods of using them
JP2004523667A
Electrets and compounds useful for electrets
JP2009526141A
Electret web containing electrostatic enhancement additives
JP2012522908A